Final answer:
To solve the Bernoulli differential equation y' - x/6y = x^9y^3, we use the substitution u = y^-2 to transform it into a linear differential equation in u. After solving for u, we revert the substitution to find y in terms of x and apply the initial condition y(1) = 1.
Step-by-step explanation:
The equation y' - x/6y = x9y3 is a Bernoulli differential equation, which is non-linear if the exponent n is neither 0 nor 1. In this case, the Bernoulli equation has n = 3. To solve it, we use the substitution u = y1-n or u = y-2. After the substitution, the differential equation becomes linear with respect to u, and we solve for u before finding y.
To perform the substitution, we differentiate u with respect to x, which gives us du/dx = -2y-3y'. Substituting y = u-1/2 and y' = -1/2 u-3/2du/dx into the original equation, we obtain a linear differential equation in u. After simplifying and integrating, we find u as a function of x. Subsequently, we convert back to find y in terms of x and apply the initial condition y(1) = 1 to find the particular solution.